DAMPAK BUDAYA ORGANISASI KOMPETENSI DAN MOTIVASI TERHADAP KINERJA ASN PADA DINAS LINGKUNGAN HIDUP KABUPATEN SITUBONDO DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Bimantara, Ario; Fandiyanto, Randika; Tulhusnah, Lusiana (Fakultas Ekonomi dan Bisnis, 2024)
The aim of this research is to analyze the influence of variablesThe Impact of Organizational Culture, Competency and Motivation on ASN Performance at the Situbondo Regency Environmental Service with Job Satisfaction as an Intervening Variable. By using the Partial Least Square (PLS) Structural equation model. Results of direct influence hypothesis testing using the Smart PLS 3.0 application. Organizational culture has a significant positive effect on ASN job satisfaction, Competency has a significant positive effect on ASN job satisfaction, Motivation has a significant positive effect on ASN job satisfaction, Organizational culture has a significant positive effect on ASN Performance, Competence has a positive but not significant effect on ASN Performance, Motivation has a significant positive effect on ASN Performance, ASN job satisfaction has a significant positive effect on ASN Performance, Organizational culture has a significant positive effect on Performance ASN through ASN job satisfaction, Competency has a significant positive effect on ASN Performance through ASN job satisfaction, and Motivation has a significant positive effect on ASN Performance through ASN job satisfaction.